An environmental impact assessment of the alternative access routes, the Western Access Route, and the Least Cost Alternative Route, to the proposed Mohale Dam, Lesotho - McMurray, Helen Frances (Department of Environmental and Geographical Science, 2016)
Bibliography: p. 54-57.